Goal Prgramming Approach in Determining Production and Delivery Decision from Two Factories - Anis Rostika Sari; I Nyoman Pujawan (Institut Teknologi Sepuluh Nopember, 2020)
Nowadays, the consumer goods industry is increasing rapidly due to several factors including market expansion, increasing number of producers, increasing competition, and high customer demands. Implementing the right production and shipping decision strategy is also very important in order to achieve the proper distribution function, efficiency, and profits received by the company. The development of retailer business in Eastern Indonesia of PT XYZ, cooking oil and branded vegetable fats food producer, especially the South Sulawesi area since 2017 to 2019 in modern trade category experienced quite high growth. However, due to product limitation constraints and delivery routes at Bitung factory, 82% supply was from Surabaya factory even though geographically Bitung factory is closer. Product variation limitations that cannot meet customer orders causes the non optimal goods expenditure from the Bitung factory, so the Bitung factory utility is very low. Longer shipping time via Surabaya factory often cause goods delay at the store resulting loss in sales volume and cash to cash cycle periods which is quite a time. Increased utilization of the Bitung factory, flexibility in ordering products, and shortened delivery speed pushed PT XYZ to optimize the Bitung factory expenditure through meeting sales targets of the South Sulawesi area by establishing a buffer warehouse in Makassar that serves as a transfer product loads consolidation of the Bitung factory and Surabaya factory to the point delivery destinations via land to customers in South Sulawesi Province. With the goal programming modeling method, the optimal transfer consolidation quantity from the two factories that can be removed from the Bitung factory is 1,831,312 cartons and the Surabaya Factory for products not produced from the Bitung factory is 158,105 cartons which then distributed through the buffer warehouse. Therefore, the expenditure of this amount will increase the utility capacity of handok machines in Bitung factory to 45% and canning machines to 12%. Sales target in South Sulawesi Area can reach 98.47% and 15% growth compared to last year. Faster delivery will be 10 to 14 days and cash to cash cyvle become 23 to 27 days.